Taxing Digital Economy through Online Marketplace in Indonesia - Tambunan, Maria R.U.D.; Rosdiana, Haula; Irianto, Edi Slamet (International Journal of Economics and Financial Issues, 2020)
This article examines the challenges on taxing digital economic performed by Indonesian government through online marketplaces engaged as the withholder of the merchants selling their products through their platform on gross basis. Online marketplace, seen as potential sector contributing to the state revenue. The research show that tax imposition on the merchant through marketplace has raised debates, since the merchant which mostly start-up and micro-business should not be taxed like established business. Small and micro-scale business registered on an online marketplace will potentially change their marketing mode to avoid tax to get higher return on the mode could be detected by government, such as social media. Further, the online marketplace has to do another risky responsibilities beside their core business; withhold the tax and remit it to the government following the prevailing law. The heat debate on the publish lead the government to postpone the policy engaging online marketplace as withholder. As the final solution, the government imposes small percentage final tax for the business who has the turn over classified as SMEs. Keywords: digital economy, tax policy, withholding tax, international tax JEL Classifications: H2, K34 DOI: https://doi.org/10.32479/ijefi.9071